Catheter directed embolectomy of right atrial clot in transit‐A case series. Issue 5 (23rd November 2020) - Verma, Isha; Chang, Eric Y; Kumar, Gautam; Sachdeva, Rajesh
Abstract: In the previous literature, the prevalence of right atrial (RA) clot‐in‐transit associated with pulmonary embolism is around 4–18% with an associated mortality of 80–100% in untreated cases. Surgical thrombo‐embolectomy has been the mainstay of treatment for stable patients but the data for percutaneous thrombo‐embolectomy is lacking in the literature. We present a series of three cases of right atrium clot‐in‐transit treated with catheter‐based therapies with Inari FlowTriever® (Inari Medical, Irvine, CA). Our three patients had different clinical profiles and presentations of right atrial clot‐in‐transit. All of the subjects had contraindications to surgical thrombo‐embolectomy and thrombolytic therapy. Catheter based embolectomy using Inari FlowTriever® was successfully performed in all the patients. As the data on this intervention is sparse, our case series highlights successful catheter based thrombo‐embolectomies in high‐risk individuals with right atrial clot in‐transit with or without pulmonary embolism.